PASTORAL TRANSHUMANCE IN MĂRGINIMEA SIBIULUI - ION VELCEA; TEODOR TODERAŞ; TRAIAN CRĂCEA; ALINA NEGOESCU (Revue Roumaine de Géographie)
This paper deals with certain aspects of a traditional activity practiced in a mountain-hilly region from southern Transylvania, called Mărginimea Sibiului. Sheep-breeding is one of the oldest activities in this area, with a significant impact on all generations, including the inhabitant of this region today. We present details of pastoral transhumance in Mărginimea Sibiului in different periods of time and nowadays, knowing that its peak was in the 18th and 19th centuries. The methodology used is based both on the analysis of a complex specialist literature and on field trips and discussions with the local authorities and the families of shepherds who currently participate in the process of transhumance. Also, in the analyses made we used statistical data obtained either from the National Institute of Statistics, or from Sibiu County Statistics Department. We established the areas of transhumance, determinant causes, restrictive factors after 1990 and the advantages of practicing transhumance.